Targeted therapies for the treatment of soft tissue sarcoma - Fuchs, Jeffrey W.; Schulte, Brian C.; Fuchs, Joseph R.; Agulnik, Mark (Frontiers in Oncology, 2023)
Soft tissue sarcomas are rare malignant tumors derived from mesenchymal cells that have a high morbidity and mortality related to frequent occurrence of advanced and metastatic disease. Over the past two decades there have been significant advances in the use of targeted therapies for the treatment of soft tissue sarcoma. The ability to study various cellular markers and pathways related to sarcomagenesis has led to the creation and approval of multiple novel therapies. Herein, we describe the current landscape of targeted medications used in the management of advanced or metastatic soft tissue sarcomas, excluding GIST. We distinguish three categories: targeted therapies that have current US Food and Drug Administration (FDA) approval for treatment of soft tissue sarcoma, non-FDA approved targeted therapies, and medications in development for treatment of patients with soft tissue sarcoma.